Influence of industry 4.0 projects on business operations: Literature and empirical pilot studies based on case studies in Poland - Bozena Gajdzik; Radosław Wolniak (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
For the past decade, Industry 4.0 has become the basis for building competitive advantage for business operations. The key technologies of Industry 4.0 are implemented in enterprises of various industries. This paper focuses on presenting the results of research on the influence of the Industry 4.0 concept on the operations of enterprises that are implementing smart manufacturing (SM) projects. The paper analyses the following areas of influence of projects on the enterprises' operations: productivity, agility and speed, quality, competitiveness and enterprise value, profitability, staff reduction, delivery improvements, vertical and horizontal integration, resource savings, reduction of operating costs, technology adaptability and quality of machine operations. The paper belongs to the research paper category. The research tool was a questionnaire. The research was carried out in the segment of steel enterprises in Poland. The results of the presented research belong to pilot research of a segment of steel industry in Poland. The main conclusion of the study is that implementation of Industry 4.0 in the Polish steel sector had a positive influence on many factors strictly connected with the innovativeness of the company. Especially, the implementation of this conception in the steel sector leads to an increase in the quality of the product and the possibility to achieve a good level of customization of the product. Those factors are very important for the steel sector potential to succeed on the competitive market. The individual SM projects that were evaluated were a form of case study. The participants of the research were employees in managerial positions and operating technological installations in steel sector enterprises. In the opinion of the surveyed (79 people), depending on the type and scope of changes implemented in the company in the direction of Industry 4.0, decision-makers expect a higher quality of processes and products, the ability to meet customer requirements-the direction of the personalization of products and services, agility and flexibility of performed operations with the use of smart technology and accuracy and precision of performance higher than in the case of manual human activities.
Keywords: 650; Industry 4.0 (I 4.0); smart manufacturing (SM); steel sector; innovativeness